Potential and efficiency of seed production of Pinus engelmannii Carr., in three seed stands of the state of Durango, Mexico - Bustamante-García, Verónica; Prieto-Ruíz, José Ángel; Merlín-Bermudes, Enrique; Álvarez-Zagoya, Rebeca; Carrillo-Parra, Artemio; Hernández-Díaz, José Ciro (Instituto de Ecología, A.C., 2012)
The potential and efficiency of seed production of Pinus engelmannii Carr. it was determined inthree seed stands in the state of Durango (El Encinal and Las Cumbres, municipality of Durango, andLa Florida, municipality of San Dimas). In each stand, 10 trees were selected, separated by a minimum